2011
DOI: 10.33541/jet.v1i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Students’ View on Grammar Teaching

Abstract: The focal point of this paper is on the view of the fifth semester students of FKIP UKI on the teaching of English grammar which was gauged through a study conducted in November 2010. The findings of the study, obtained via quantitative and qualitative approaches, revealed that a majority of the respondents basically viewed grammar is important in their study of English. They also viewed knowledge of grammar plays an important role in writing, but has no significant role in speaking. In addition, the responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…All these assertions are conducive to a communicative take to grammar teaching. Although the findings correspond with some related studies (Incecay & Dollar, 2011) in which the respondents were in favor of learning grammar communicatively, Male (2011), reported that learners preferred formal presentation of grammar structures. The participants in Male"s study "viewed knowledge of grammar to play an important role in writing, but has no significant role in speaking" (Male, 2011, p. 58).…”
Section: Grammar As An Interactional Toolsupporting
confidence: 88%
See 3 more Smart Citations
“…All these assertions are conducive to a communicative take to grammar teaching. Although the findings correspond with some related studies (Incecay & Dollar, 2011) in which the respondents were in favor of learning grammar communicatively, Male (2011), reported that learners preferred formal presentation of grammar structures. The participants in Male"s study "viewed knowledge of grammar to play an important role in writing, but has no significant role in speaking" (Male, 2011, p. 58).…”
Section: Grammar As An Interactional Toolsupporting
confidence: 88%
“…This was also supported by exploration on learners" beliefs. Male (2011) reported that the majority of participants in his study favored explicit to implicit teaching to grammar. The findings as for an explicit or implicit grammar teaching mode reflect the controversy on this issue and call for a mediation, balancing implicitness and explicitness takes.…”
Section: Balance Between Explicit and Implicit Instruction Of Grammarmentioning
confidence: 97%
See 2 more Smart Citations
“…Some teachers teach grammar explicitly while others do implicitly (Ellis 2014;Ellis et al 2009;Nazari 2013). In Indonesia, where English is still considered as a foreign language, grammar holds a quite important role (Male 2011), especially for Junior High School and Senior High School students, since the high-stake English National Examination (Umam 2011;Sutari 2017) covers grammar-related questions. The high-stake test leads to negative washback effect, as English teachers are pushed to devote most of the teaching times for test preparations and strategies (Sukyadi and Mardiani 2011;Sutari 2017).…”
Section: A Introductionmentioning
confidence: 99%